AKTIVITAS ANTIOKSIDAN KRIM EKSTRAK SARI TOMAT (Solanum lycopersicum L.) - Alissya Swastika NSP; Mufrod Mufrod; Purwanto Purwanto (Faculty of Pharmacy, Universitas Gadjah Mada, 2013)
Premature aging skin condition characterized by dry, scaly, rough and accompanied by the appearance of wrinkles and dark spots or blemishes has become to be a women fearing thing, especially among women in reproductive age. Factors causing premature aging are internal factors (health, stamina, stress and hormonal changes) and external factors (free radicals, sunlight and pollutants). Free radicals can be prevented by antioxidant compounds either synthetic or natural materials. Tomato is one of the natural antioxidants. The most antioxidant content in tomato is lycopene. Tomato is used in the form of tomato juice made by extraction method. Tomato in their use directly is less effective so that tomato is made in the form of cream. Cream compositions were made by variation concentration of tomato juice (5%, 10%, 15%, and 20%). The antioxidant activity was tested by DPPH method. Physical stability parameters tested in this research were homogenity, viscosity, dispersive power, adhesion, cream separation ratio and pH. Data were analyzed by Kolmogorov-Smirnov test, one way ANOVA test and Tukey test. Organoleptic test data, the physical properties of the cream, and the type of emulsion were analyzed descriptively .The results showed that tomato juice has antioxidant activity with IC50 value 2,69%. The increase in the concentration of tomato juice gave significantly different results in all formulas except the formulas III and IV that were not significantly different. The IC50 values cream of tomato juice were 9,12%; 708%; 3,61%; and 2,85% respectively for the cream with tomato extract concentration of 5%, 10%, 15%, 20%. This showed that the higher the concentration of tomato juice, the higher the antioxidant activity as indicated by the lower of IC50 value. The increase in the concentration of tomato juice as active ingredients provided significantly different results for difference antioxidant activity, color, and smell, but did not cause significant differences in the consistency, viscosity, dispersive power, time and pH.